Finance and HR as Gen Z Stressors: Palangka Raya University Students' Views - Aprilita, Aprilita; Damayanti, Nurlia Eka; Mahrita, Ani (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
In recent years, increasing suicide rates among college students have demonstrated a mental health crisis that needs to be taken seriously. This phenomenon highlights that academic pressure is just one of many social, economic, and cultural pressures that affect students. Therefore, it is important to understand the factors that trigger these issues and provide adequate mental health support. Some suicide incidents involving students in Indonesia emphasize the urgency of addressing this mental health issue. Research shows that life events or stressors, such as stress, anxiety, and depression, have a significant impact on driving suicidal ideation. Factors such as academic pressure, financial burdens, and lack of social support also play an important role in the stress levels experienced by college students. The research "Stress Stimulus Analysis of Palangka Raya University Students" aims to understand the influence of financial factors and human resources on student stress levels. It is hoped that this research will not only provide insight into the factors that influence students' mental well-being but will also provide a basis for developing more effective intervention strategies in dealing with stress levels among students.